Current Models for Transcriptional Regulation of Secondary Cell Wall Biosynthesis in Grasses - Rao, Xiaolan; Dixon, Richard A. (Frontiers in Plant Science, 2018)
Secondary cell walls mediate many crucial biological processes in plants including mechanical support, water and nutrient transport and stress management. They also provide an abundant resource of renewable feed, fiber and fuel. The grass family contains the most important food, forage and biofuel crops. Understanding the regulatory mechanism of secondary wall formation in grasses is necessary for exploiting these plants for agriculture and industry. Previous research has established a detailed model of the secondary wall regulatory network in the dicot model species Arabidopsis thaliana. Grasses, branching off from the dicot ancestor 140-150 million years ago, display distinct cell wall morphology and composition, suggesting potential for a different secondary wall regulation program from that established for dicots. Recently, combined application of molecular, genetic and bioinformatics approaches has revealed more transcription factors involved in secondary cell wall biosynthesis in grasses. Compared with the dicots, grasses exhibit a relatively conserved but nevertheless divergent transcriptional regulatory program to activate their secondary cell wall development and to coordinate secondary wall biosynthesis with other physiological processes.